Cell-based delivery of glucagon-like peptide-1 using encapsulated mesenchymal stem cells. (17th September 2012) - Wallrapp, Christine; Thoenes, Eric; Thürmer, Frank; Jork, Anette; Kassem, Moustapha; Geigle, Peter
Abstract : Glucagon-like peptide-1 (GLP-1) CellBeads are cell-based implants for the sustained local delivery of bioactive factors. They consist of GLP-1 secreting mesenchymal stem cells encapsulated in a spherically shaped immuno-isolating alginate matrix. A highly standardized and reproducible encapsulation method is described for the manufacturing of homogeneous CellBeads. Viability and sustained secretion was shown for the recombinant GLP-1 and the cell endogenous bioactive factors like vascular endothelial growth factor, neurotrophin 3 (NT-3) and glial cell line-derived neurotrophic factor. Manufacturing and quality control is performed in compliance with good manufacturing practice and fulfils all regulatory requirements for human clinical use. GLP-1 CellBeads combine the neuro- and cardioprotective properties of both GLP-1 and mesenchymal stem cells. First promising results were obtained from preclinical studies and an ongoing safety trial in humans but further studies have to prove the overall potential of CellBead technology in cell-based regenerative medicine.